THE ANALYSIS OF MULTIMODAL IN COFFEE ADVERTISEMENT - Sarah Nasution (Jurnal Warta Dharmawangsa, 2023)
ABSTRACT- Coffee commercials are always full of persuasion. Coffee is an inseparable part of Indonesian society. Due to drinking coffee for everyone in Indonesia, drinking coffee has become a tradition inherent in social culture. This study aims to analyse multimodal visually in coffee advertisements circulating in Indonesia. This study used a qualitative descriptive method to analyse the data based on Kress and Van Leeuwen. The results of this study show how the multimodal visual process is shown in the coffee advertisement.Keywords: Analysis, Coffee Advertisement, Multimodal, Visual